Studies of the diffractive photoproduction of isolated photons at HERA - Abramowicz, Halina; Lisovyi, Mykhailo (Physical review, 2017)
The photoproduction of isolated photons has been measured in diffractive events recorded by the ZEUS detector at HERA. Cross sections are evaluated in the photon transverse-energy and pseudorapidity ranges 5<EγT<15 GeV and −0.7<ηγ<0.9, inclusively, and also with a jet with transverse energy and pseudorapidity in the ranges 4<EjetT<35 GeV and −1.5<ηjet<1.8, using a total integrated electron-proton luminosity of 456 pb−1. A number of kinematic variables were studied and compared to predictions from the rapgap Monte Carlo model. An excess of data is observed above the rapgap predictions for zmeasP>0.9, where zmeasP is the fraction of the longitudinal momentum of the colorless “Pomeron” exchange that is transferred to the photon-jet final state, giving evidence for direct Pomeron interactions.
Gesehen am 26.09.2018